Influência dos preços dos principais grãos da alimentação de suínos no preço da carne porcina nos estados de Goiás, Minas Gerais e Paraná - Oliveira Júnior, João Ricardo de (2021)
In pig farming, animal nutrition is considered an important component of the production costs representing about 70% of rearing and fattening activity. This input is based on three important agricultural products: corn, soybeans and sorghum. That said, the knowledge of the interrelationships between inputs’ prices and other components of animal feed allows to draw some guidelines for planning and management of pig farmers especially for the decisions making that involve production that can expanding the possibilities of financial returns. Thus, the main objective of this master thesis was to analyze the influence of corn, soy and sorghum prices on the pork price in the states of Goiás, Minas Gerais and Paraná, Brazil. The methodology used involved verifying the behavior and order of integration of the variables. As well as, the investigation of the degree of magnitude and speed of adjustment of pork prices to highs and lows alterations in these commodities prices. In addition, the hypothesis of asymmetry in prices was verified. In the end, the causal relationship between prices was accurate. The econometric models used in this master thesis were Engle-Granger cointegration, ECM, TAR, M-TAR and Granger causality. Consequently, due to the common results found between the states of Goiás, Minas Gerais and Paraná, pork price respond equally to changes in the prices of corn, soy and sorghum, with similar behaviors in the long term. As well, that the short-term price path towards long-term equilibrium is slow, with the late transfer of corn, soybeans and sorghum prices of pork price. In addition, it has been assumed that a hypothetical increase in grain prices would lead to a significant increase in pork prices when using sorghum and soy in pig feed in Minas Gerais and Goiás, whereas in Paraná it would be when using corn and soy. Also, the corn price can be considered a good predictor for pork price in Minas Gerais and Paraná. In Goiás the pork prices are a good predictor for variations in sorghum prices. And in Paraná the pork price is established as a good predictor for variations in soybeans prices.